DESIGN OF AN ANDROID-BASED NEW STUDENT AND SANTRI REGISTRATION APPLICATION AT BABUL FUTUH PANDAAN ISLAMIC BOARDING SCHOOL - Muhammad Damiri Ilyas; Cahya bagus Sanjaya (BIOS: Jurnal Informatika dan Sains, 2023)
This research aims to develop an Android-based information system application that is appealing, legitimate, practical, and effective in facilitating the registration process for new students in grades VII and X at Babul Futuh Islamic Boarding School at the beginning of the new academic year. The main objective of this application is to enhance the quality and efficiency of the New Student Admission (PPDB) process. This research will follow the waterfall or sequential linear development model, employing observation and interviews as data sources involving teachers, students, and registration committee members. Through this approach, the application will consider positive potentials, constraints, and opportunities to shape an efficient registration system. The research instrument consists of a questionnaire to be filled out by prospective students. It is expected that the outcomes of this research will yield an Android-based information system application that is appealing, legitimate, practical, and effective. This application is anticipated to strengthen communication between the boarding school's admission committee and prospective students during the registration process, ultimately leading to a positive assessment and supporting the growth of the boarding school in the future.